PENINGKATAN MINAT BACA INTENSIF BERBASIS CERITA RAKYAT MELALUI MEDIA AUDIO VISUAL PADA SISWA KELAS V SEKOLAH DASAR - Rochiana, Rina (INOPENDAS: Jurnal Ilmiah Kependidikan, 2023)
This study is to describe research on the effect of the Numbered Head This research is motivated by the decline in reading interest in students which results in low student knowledge. This study aims to increase students' reading interest and students' grammar and attitudes change in a positive direction through a lot of reading. The theoretical basis used in this research is the theory of reading interest, the theory of technological literacy, the theory of audio-visual media and the theory of folklore. The method used is a qualitative approach using descriptive methods through interview techniques. The results of this study indicate that the use of folklore-based audio-visual media can increase intensive reading interest in fifth grade elementary school students. So that students are more interested in listening and reading through the use of audio-visual media downloaded from the YouTube application. The discussion suggests that there are difficulties at the beginning when inviting students to learn to watch audio-visual media based on folklore that has been given because of the assumption that the media is only given to early childhood, but over time students are able to follow and students' reading abilities can improve. The conclusion of this study is that literacy is important for every human being, including age and position, the use of audio-visual media downloaded through the YouTube application is proof that technological developments can have a positive impact on students when an educator is able to provide positive examples and habits as well.